2005
DOI: 10.1097/01.alc.0000175074.70807.fd
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and the Body???s Biological Clock

Abstract: This review summarizes new findings on the bidirectional interactions between alcohol and the clock genes, underlying the generation of circadian rhythmicity. At the behavioral level, both adult and perinatal ethanol treatments after the free-running period and light response of the circadian clock in rodents; genetic ethanol preference in alcohol-preferring rat lines is also associated with alterations in circadian pacemaker function. At the neuronal level, it has been shown that ethanol consumption alters th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(131 citation statements)
references
References 78 publications
3
125
0
3
Order By: Relevance
“…Sucrose (0.45 and 5%) and quinine (10 and 20 mg/dl) preference was measured in a two-bottle free-choice test vs water. Each dose was offered for 3 days with the position of the bottles being changed and weighed daily (Spanagel et al, 2005).…”
Section: Taste Preference Testmentioning
confidence: 99%
“…Sucrose (0.45 and 5%) and quinine (10 and 20 mg/dl) preference was measured in a two-bottle free-choice test vs water. Each dose was offered for 3 days with the position of the bottles being changed and weighed daily (Spanagel et al, 2005).…”
Section: Taste Preference Testmentioning
confidence: 99%
“…Per2 Brdm1 mutant animals display a 'hyperglutamatergic' state in their CNS, i.e. augmented extracellular glutamate levels (Spanagel et al 2005b). Interestingly, it has been shown that an intracerebroventricular infusion of L-glutamate may prolong the ethanol-induced LORR duration in mice (Ferko 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we were able to demonstrate that mutations in Per1 and Per2 genes can modulate the effects of drugs of abuse in a different manner (Abarca, Albrecht & Spanagel 2002;Spanagel et al 2005aSpanagel et al , 2005bZghoul et al 2007;Perreau-Lenz & Spanagel 2008;Spanagel 2009). In particular, we established that although mice mutant in the Per2 gene (Per2 Brdm1 ) display enhanced alcohol consumption and preference (Spanagel et al 2005a), Per1 Brdm1 mutant mice did not show such an enhancement in alcohol drinking behavior (Zghoul et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Как показывают результа-ты экспериментальных исследований, одной из причин нарушений сна при АСП является срыв регуляции цир-кадных ритмов вследствие повреждающего воздействия алкоголя на супрахиазматическое ядро гипоталамуса, ответственного в т. ч. и за чередование периодов сна и бодрствования [26]. Наряду с этим на формирование патологии сна дополнительное влияние могут оказывать поведенческие нарушения и психические расстройства, свойственные данному синдрому [27].…”
Section: вопросы современной педиатрииunclassified